LEARNING PERFECT ENGLISH REQUIRES THE ACCURACY OF VOCABULARY, GRAMMAR AND PRONUNCIATION. (E Conference Zone, 2022)
Learning perfect English requires the correct of vocabulary, grammar, and pronunciation. It can say that accuracy is the ability to produce sentence using correct grammar and vocabulary. Teacher who concentrate on accuracy help their students to produce grammatically correct written and spoken English. Fluency can be thought of the ability to keep going when speaking spontaneously. When fluently speaking students should be able to get the message across with whatever resources and abilities they have got, regardless of the grammatical and other mistakes.